2004
DOI: 10.1111/j.0013-9580.2004.09604.x
|View full text |Cite
|
Sign up to set email alerts
|

Isobolographic and Subthreshold Analysis of Interactions among Felbamate and Four Conventional Antiepileptic Drugs in Pentylenetetrazole‐induced Seizures in Mice

Abstract: Summary:Purpose: Despite possibility of idiosyncratic reaction development, felbamate (FBM) is recommended in LennoxGastaut syndrome and partial refractory epilepsy. The aim of this study was to evaluate the profile of interactions between FBM and four conventional antiepileptic drugs (AEDs): clonazepam (CZP), ethosuximide (ESM), phenobarbital (PB), and valproate (VPA), in pentylenetetrazole (PTZ)-induced convulsions in mice, a model of myoclonic seizures in humans.Methods: Data obtained from PTZ-evoked seizur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Similarly, additivity was reported for the combina-tions of riluzole with carbamazepine, phenytoin, phenobarbital and valproate in the maximal electroshock seizure test in mice [20] . In contrast, the combinations of felbamate with valproate, phenobarbital, clonazepam and ethosuximide in the pentylenetetrazole-induced seizure model exerted antagonistic interactions with isobolographic transformation of data, although the subthreshold method indicated that antiepileptic drugs potentiated their anticonvulsant effects in mice [21] .…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Similarly, additivity was reported for the combina-tions of riluzole with carbamazepine, phenytoin, phenobarbital and valproate in the maximal electroshock seizure test in mice [20] . In contrast, the combinations of felbamate with valproate, phenobarbital, clonazepam and ethosuximide in the pentylenetetrazole-induced seizure model exerted antagonistic interactions with isobolographic transformation of data, although the subthreshold method indicated that antiepileptic drugs potentiated their anticonvulsant effects in mice [21] .…”
Section: Discussionsupporting
confidence: 59%
“…0.7, and sub-additivity (antagonism) is evident if the sum of ED 50 fractions is 1 1.3 [18,19] . This experimental procedure has been described in detail in our earlier studies [20][21][22] .…”
Section: Isobolographic Transformationmentioning
confidence: 99%
“…Oxcarbazepine was supra-additive with clonazepam, phenytoin, and valproate in the MES model, lamotrigine was supra-additive with topiramate and valproate in the MES model, tiagabine was supra-additive with valproate in the MES model, and tiagabine with gabapentin was supraaddictive in the MES model. [25][26][27][28][29][30][31][32][33][34][35][36][37] Gabapentin acted synergistically with carbamazepine, valproate, phenytoin, phenobarbital, and lamotrigine in the MES model. 39 SUMMARY Animal models of seizures have helped to identify new AEDs effective in humans and can provide useful information about the possible effects of specific combination therapies.…”
Section: Polytherapy Studies In Animalsmentioning
confidence: 98%
“…Czuczwar et al have used isobolographic analysis to assess the synergism and antagonism of AEDs used in combination in rodent models. [25][26][27][28][29][30][31][32][33][34][35][36][37] Using this technique, one can determine the relative potency of each drug presented in a mixture as x/X ϩ y/Y ϭ 1, where x and y are the doses of the drugs in mixture that exert a desired effect (usually 50% effect) and X and Y are doses of drug used separately, which produce the same effect. The x/X and y/Y are relative potencies of the respective drugs used in the preparation.…”
Section: Polytherapy Studies In Animalsmentioning
confidence: 99%
“…9 Concomitant administration of AEDs (phenytoin, phenobarbitone, sodium valproate, CBZ) and diazepam or clonazepam have produced variety of drug interactions in clinical as well in vivo and in vitro animal studies. [10][11][12][13] As a few such studies have been reported, the present experimental study was undertaken with four conventional AEDs, phenytoin, CBZ, sodium valproate, and phenobarbitone, combined with two BZD diazepam or clonazepam, to find out whether diazepam or clonazepam modify the effect of these AEDs when they are co-administered. i.e., whether any significant drug interaction is possible between diazepam, clonazepam, and AEDs in a single dose.…”
Section: Introductionmentioning
confidence: 99%